Magnetic molecularly imprinted polymer for determination of neonicotinoid pesticides in honey by UHPLC-QQQ-MS/MS / Ahmed Qasim Abdulhussein - Ahmed Qasim , Abdulhussein (2022)
In this work, new selective and sensitive dual-template molecularly imprinted polymer nanoparticles (MIPs1 and MIPs2) were synthesised for the simultaneous extraction and clean-up of four neonicotinoid pesticide residues (nitenpyram, imidacloprid) and (thiamethoxam, thiacloprid) from honey samples. Ultra high performance liquid chromatography-tandem mass spectrometry triple-quadrupole UHPLC-MS/MS (QqQ) was used for the selectivity and sensitivity analysis and to determine the pesticides in the honey samples successfully. A multi-template MIPs was synthesised using precipitation polymerisation method with functionalised Fe3O4 nanoparticles. Sorbent MIPs1 was prepared by polymerisation of nitenpyram and imidacloprid as a template with 2-vinylpyridine as a functional monomer. For sorbent MIPs2, thiamethoxam and thiacloprid were utilised as a template with methacrylic acid as a functional monomer. Both MIPs used ethylene glycol dimethacrylate (EGDMA) as cross-linker and 4,4’-azobis (4-cyanovaleric acid) as the initiator. Characterisation of the polymers was performed by Fourier transform infrared spectroscopy, scanning electron microscopy, and thermogravimetric analysis. The adsorption kinetic curve, adsorption isotherm, and selective adsorption were measured by a static method. Pseudo-second-order kinetic model best explained the adsorption kinetics. The adsorption data fitted well into the linearized Freundlich equation (R2 = 0.999). The R2 values obeyed the Langmuir isotherm model indicating that binding occurred on the homogeneous sites. Scatchard plot analysis of MIPs demonstrated linearity, indicating the presence of homogenous sites. To maximise the extraction performance, several parameters such as MIPs sorbent amounts, extraction time and sample pH were optimised prior to UHPLC-MS/MS analysis. Sorbent MIPs1 revealed a much higher affinity for nitenpyram and imidacloprid than structurally similar analogues thiamethoxam (α = 17.79, 13.66) and thiacloprid (α = 14.63, 11.23), while sorbent MIPs2, displayed a much higher affinity for thiamethoxam and thiacloprid over structurally equivalent nitenpyram (α = 6.407, 10.97) and imidacloprid (α = 8.297, 8.816) analogues. The method limit of detection (LOD) and limit of quantification (LOQ) for pesticides from light and dark honey ranged from 0.03 μg kg-1 - 0.08 μg kg-1 and 0.06 μg kg-1 - 0.12 μg kg-1, respectively. The intra-day and inter-day precision (RSD, %) ranged from 0.6% to 2.0% and 5.0% to 12.0%, respectively. The proposed method was successfully applied for analysis of the four neonicotinoids in honey samples with high recoveries ranging from 94.3% to 108.0%.